Towards an inclusive green Bangladesh: Occasional speeches by Governer, Bangladesh Bank 2013-2015 - Rahman Atiur (Bangladesh: Pathak Shamabesh, 2018)
This volume speaks about many changes in the economy and financial sector of Bangladesh , some of which reflect tectonic transitions. In particular, the seeds of transformative changes sown by the central bank of Bangladesh under his ledership by nudging finance toward equity, inclusion and envioronment have given birth to trees that deserve to be nurtured over coming years. While making this remarkable journey Governor Rahman had to speak a lot to the stakeholders both home and abroad. This volume narrates this fascinating journey of a regulator who made a sincere attempt at changing the focus of a central bank towards inclusion and sustanibility of finance.
Global economics issues -- Macroeconomics issues and the bangladesh economy -- Monetary, Fiscal and exchange rate policies -- prudential regulation, supervision, risk management, money langundering and financial stability -- Financial inclusion, microfinance, agriculture and SME lending -- CSR and green banking issues --Digital bangladesh and IT in banks -- Other economic and social issues -- Epilogue
inclides index
Keywords: Economics -- Environment; Sustainable Development -- Bamgladesh; Green Banking -- Bangladesh; Economy -- Financial Sector -- Bangladesh